Molecular genetics of renal ciliopathies. (30th June 2021) - Barroso-Gil, Miguel; Olinger, Eric; Sayer, John A.
Abstract : Renal ciliopathies are a heterogenous group of inherited disorders leading to an array of phenotypes that include cystic kidney disease and renal interstitial fibrosis leading to progressive chronic kidney disease and end-stage kidney disease. The renal tubules are lined with epithelial cells that possess primary cilia that project into the lumen and act as sensory and signalling organelles. Mutations in genes encoding ciliary proteins involved in the structure and function of primary cilia cause ciliopathy syndromes and affect many organ systems including the kidney. Recognised disease phenotypes associated with primary ciliopathies that have a strong renal component include autosomal dominant and recessive polycystic kidney disease and their various mimics, including atypical polycystic kidney disease and nephronophthisis. The molecular investigation of inherited renal ciliopathies often allows a precise diagnosis to be reached where renal histology and other investigations have been unhelpful and can help in determining kidney prognosis. With increasing molecular insights, it is now apparent that renal ciliopathies form a continuum of clinical phenotypes with disease entities that have been classically described as dominant or recessive at both extremes of the spectrum. Gene-dosage effects, hypomorphic alleles, modifier genes and digenic inheritance further contribute to the genetic complexity of these disorders. This review will focus on recent molecular genetic advances in the renal ciliopathy field with a focus on cystic kidney disease phenotypes and the genotypes that lead to them. We discuss recent novel insights into underlying disease mechanisms of renal ciliopathies that might be amenable to therapeutic intervention.